PENGARUH KEPRIBADIAN, SELF EFFICACY DAN LOCUS OF CONTROL TERHADAP KINERJA KARYAWAN - Edi Siregar; Natalia Anggina (Jurnal Manajemen, 2020)
This study aims to determine whether there is a significant effect of personality, self-efficacy and locus of control on employee performance. Data collected from distributing questionnaires to 85 respondents who are part of PT. Pegadaian (Persero) Kebayoran Lama Branch Office. The research methodology used is quantitative processing of questionnaire data and observations with multiple linear regression analysis methods. Based on the results of the study, it is known that simultaneously personality, self-efficacy and locus of control have a significant influence on employee performance. Personality and self-efficacy partially have a significant effect on employee performance. Locus of control partially has no effect on employee performance. The percentage of the influence of personality, self-efficacy and locus of control on employee performance is 18.9%, the remaining 81.1% is influenced by other variables not included in this study